ETNOMATEMÁTICA E A VALORIZAÇÃO DA CULTURA AFRO NAS AULAS DE MATEMÁTICA E HISTÓRIA ATRAVÉS DAS TRANÇAS AFRICANAS: UM PROJETO INTERDISCIPLINAR (REMUNOM, 2025)
RESUMO This article presents the experience of applying an interdisciplinary project developed in the disciplines of Mathematics and History in a public school in Jerônimo Monteiro – ES, focusing on the valorization of Afro-Brazilian culture through the ethnomathematical approach. Entitled Ethnomathematics and the appreciation of Afro culture in Mathematics and History classes through African braids, the project had the specific objectives of promoting dialogue between disciplines, presenting the concept of ethnomathematics, exploring the different types of African braids and addressing Afro culture as a pedagogical instrument to combat prejudice and bullying. Through the analysis of geometric patterns, symmetries and sequences present in the braids, it was possible to integrate mathematical and historical knowledge in a meaningful and culturally contextualized way. The results revealed a high level of engagement and learning on the part of students and teachers, showing that the insertion of traditional and identity knowledge in the curriculum contributes to a more inclusive, critical education aligned with the guidelines of the National Common Curricular Base (BNCC) and Law No. 10,639/2003. It is concluded that ethnomathematics, by recognizing and valuing the knowledge of different cultures, strengthens the role of the school in promoting equity and respect for diversity.  Keywords: Ethnomathematics. Afro-Brazilian culture. Interdisciplinarity. Anti-racist education. African braids.